ANALISA PENGUATAN MATA PISAU MESIN PENCACAH SAMPAH ORGANIK DENGAN PROSES HEAT TREATMENT BERTINGKAT - Mohamad Abdul Jaelani; Muhamad Fajar Sidiq; Galuh Renggani Wilis (Universitas Muria Kudus, 2021)
Garbage has been considered useless and disgusting. The problem of pollution due to the presence of waste requires processing and management to overcome it, one of which is composting. The waste chopper is a tool that makes it easy to destroy and speed up the composting process of organic waste. The progress of the industrial sector cannot be separated from the development of the tool industry or blacksmiths, both large and small. In the manufacture of blades or blacksmith himself experienced several problems, among many consumers who complains of sharpness and strength of the blades are manufactured. There are several factors that affect the sharpness and strength of the blades, including during the heat treatment process. This study used an experimental method with ST 41 steel as the material. Carburizing process using coconut shell charcoal powder at a temperature of 875 ℃, hardness test and wear test material and the salt water quenching media. The highest average hardness test value was produced by the carburising and hardening processes with a hardness value of 599.7 VHN, while the lowest wear test value was found in the carburising and hardening process, namely 0,0000767 mm³ / kg.m.